Acrylic resin film, polarizing plate, and liquid crystal display panel
The development of an acrylic resin film with specific properties addresses the challenges of maintaining transparency and preventing blocking in polarizer protective films for liquid crystal display devices, ensuring excellent heat resistance and anti-blocking performance.
Patent Information
- Application Number
- JP2024542069
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-02-28
- Filing Date
- 2024-02-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-02-27
AI Technical Summary
Existing methods for improving the durability of polarizer protective films in liquid crystal display devices, such as adding silica particles to norbornene-based resin films, face challenges in maintaining transparency and preventing blocking during film roll storage, especially with the increasing size and definition of liquid crystal display panels.
An acrylic resin film with a glass transition temperature of 120° C. or higher, a controlled sum of Kurtosis Rku on both sides (10 to 50), and an internal haze of 1.0% or less, incorporating an anti-blocking agent with acrylic cross-linked particles of specific size and content, is developed to enhance heat resistance, transparency, and anti-blocking properties.
The acrylic resin film achieves excellent transparency and heat resistance while effectively preventing blocking during film roll storage, ensuring high-quality performance in liquid crystal display devices.
Smart Images

Figure 0007648852000001 
Figure 0007648852000002 
Figure 0007648852000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic resin film, a polarizing plate, and a liquid crystal display panel. [Background technology]
[0002] In a liquid crystal display device, two polarizing plates are usually arranged on both sides of a liquid crystal cell. A polarizing plate is generally used in which a polarizer protective film for protecting a polarizer is attached to both sides of the polarizer with an adhesive. The polarizer protective film is required to have high transparency, and an optical film made of a cellulose-based material is often used.
[0003] It has been proposed to use optical films made of acrylic resins or norbornene resins as polarizer protective films for the purpose of improving durability, etc. However, these optical films are prone to wrinkles and wrinkle marks due to contact between films when wound into a roll, and as a method for solving this problem, a method has been proposed in which fine particles such as silica particles are added to a norbornene resin film to ensure roll winding properties (slipperiness) (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 074513 Summary of the Invention [Problem to be solved by the invention]
[0005] Although the method described in Patent Document 1 can solve the problem of wrinkles and wrinkle marks occurring during winding, the inventors' research has revealed that, as the film quality standard improves due to the higher resolution and larger area of liquid crystal display panels, defects occur due to the film being wound tightly during storage in a film roll. The inventors also attempted to solve the above phenomenon by adding silica to an acrylic resin film using the method described in Patent Document 1, but found that the conventional method had difficulty in satisfying the requirements for an optical film, such as increasing haze.
[0006] The present invention has been made to solve the above problems. An object of the present invention is to suppress blocking during storage of a film roll while maintaining the heat resistance and transparency of an acrylic resin film. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems and have completed the present invention.
[0008] That is, one aspect of the present invention relates to the following.
[0009] [1] An acrylic resin film containing an acrylic resin as a main component, the acrylic resin film having a glass transition temperature of 120°C or higher, a sum of kurtosis Rku on both sides of the acrylic resin film being 10 or more and 50 or less, and an internal haze being 1.0% or less.
[0010] [2] The acrylic resin film according to [1], wherein the static friction coefficient between one surface and the other surface of the acrylic resin film is 0.8 or less.
[0011] [3] The acrylic resin film according to [1] or [2], wherein the acrylic resin contains at least one type of ring structure selected from a lactone ring structure, a glutarimide structure, a glutaric anhydride structure, an N-substituted maleimide structure, and a maleic anhydride structure.
[0012] [4] The acrylic resin film according to [1] or [2], wherein the acrylic resin has a syndiotacticity, expressed as a triad, of 54% or more.
[0013] [5] The acrylic resin film according to any one of [1] to [4], wherein the acrylic resin film contains an antiblocking agent, and the antiblocking agent contains acrylic crosslinked particles having an average particle diameter of 0.1 μm or more and 2.5 μm or less.
[0014] [6] The acrylic resin film according to [5], wherein the antiblocking agent contains acrylic crosslinked particles having an average particle size of 0.1 μm or more and 2.0 μm or less.
[0015] [7] The acrylic resin film according to [5] or [6], containing 0.05% by weight or more and 0.9% by weight or less of the acrylic crosslinked particles.
[0016] [8] The acrylic resin film according to any one of [1] to [7], which has a dimensional change rate of -2.0% or more and -0.1% or less when left to stand for 120 hours under an atmosphere of 85°C and 85% RH.
[0017] [9] A polarizing plate comprising the acrylic resin film according to any one of [1] to [8].
[0018]
[10] A liquid crystal display panel comprising the polarizing plate according to [9]. Effect of the Invention
[0019] According to the present invention, it is possible to provide an acrylic resin film which is excellent in transparency and heat resistance and which can prevent blocking during storage of a film roll. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] An embodiment of the present invention will be described, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims, and embodiments and examples obtained by appropriately combining the technical means disclosed in different embodiments and examples are also included in the technical scope of the present invention. All academic literature and patent documents described in this specification are incorporated by reference in this specification. Unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".
[0021] (Acrylic resin film) The acrylic resin film of this embodiment is an acrylic resin film mainly composed of an acrylic resin, characterized in that the glass transition temperature of the acrylic resin film is 120° C. or higher, the sum of the kurtosis Rku on both sides of the acrylic resin film is 10 to 50, and the internal haze is 1.0% or less. In this way, by controlling the sum of the kurtosis on both sides of the film to a predetermined value while using an acrylic resin as the main component and further controlling the internal haze to a predetermined value, an acrylic resin film excellent in heat resistance and transparency and excellent in anti-blocking properties during storage in a film roll can be obtained.
[0022] The glass transition temperature of the acrylic resin film of this embodiment is 120°C or higher. It is preferably higher than 120°C, more preferably 121°C or higher, even more preferably 122°C or higher, and particularly preferably 123°C or higher. When the glass transition temperature of the acrylic resin film is 120°C or higher, the dimensional change rate of the stretched film in a high-temperature environment is reduced. In practical use, the acrylic resin film of this embodiment is often laminated with other films, and a small dimensional change rate can suppress the occurrence of distortion or warping caused by the difference in dimensional change rate between the acrylic resin film and other laminated films.
[0023] The glass transition temperature of the acrylic resin constituting the acrylic resin film is preferably 120°C or higher, more preferably over 120°C, even more preferably 121°C or higher, even more preferably 122°C or higher, and particularly preferably 123°C or higher.
[0024] Here, as the acrylic resin having a glass transition temperature of 120° C. or more, an acrylic resin having a ring structure in the main chain can be suitably used. For example, the ring structure can be at least one selected from the group consisting of glutarimide ring, lactone ring, maleic anhydride, maleimide, and glutaric anhydride. These can provide heat resistance. Among them, it is particularly preferable that the ring structure is glutarimide in terms of ease of production, cost, and quality stability against moisture.
[0025] The content of the ring structure in the acrylic resin having a glass transition temperature of 120° C. or higher is preferably in the range of 2% by weight to 80% by weight, more preferably in the range of 3% by weight to 60% by weight. A content of the ring structure within this range is preferable because both the glass transition temperature and the thickness direction retardation Rth are good. The content of the ring structure in the acrylic resin is 1 The molar ratio of the target ring structure portion to the other portion can be measured using H-NMR, and the molar ratio can be calculated by weight conversion. The acrylic resin having a glass transition temperature of 120° C. or more is the main component of the acrylic resin film, and is contained in an amount of more than 50% by weight in 100% by weight of the acrylic resin film. Among them, 70% by weight or more is preferable, 80% by weight or more is more preferable, 85% by weight or more is even more preferable, and 90% by weight or more is particularly preferable in 100% by weight of the acrylic resin film.
[0026] As the acrylic resin having a glass transition temperature of 120° C. or higher, an acrylic resin having no ring structure in the main chain may be used.
[0027] The internal haze of the acrylic resin film of this embodiment is 1.0% or less. In particular, the internal haze is preferably 0.7% or less, more preferably 0.5% or less, and particularly preferably 0.3% or less. By having an internal haze of 1.0% or less, the quality when mounted on a liquid crystal panel is good.
[0028] In this specification, internal haze is defined as the haze value measured using a haze meter (turbidity meter) with the obtained film placed in a glass cell for measuring liquid and the surrounding area filled with pure water.
[0029] The haze of the acrylic resin film of the present embodiment is not particularly limited as long as the internal haze is within the above-mentioned range. From the viewpoint of transparency, the haze is preferably 3.0% or less, more preferably 2.0% or less, and even more preferably 1.0% or less.
[0030] By setting the sum of the kurtosis Rku on both sides of the acrylic resin film to 10 or more and 50 or less, blocking during storage of the film roll can be effectively prevented. This can prevent defects that may occur in the film. Here, if the sum of the kurtosis Rku on both sides of the acrylic resin film is less than 10, blocking occurs due to tight winding during storage of the film roll, resulting in film defects. This tendency becomes more pronounced during storage of a long (e.g., 8000 m) film roll. Therefore, only a fixed length (e.g., 4000 m) acrylic resin film can be wound, and the yield decreases. In addition, even if the acrylic resin film is of a fixed length, the inner acrylic resin film undergoes plastic deformation during storage of the film roll, making it impossible to use the plastically deformed acrylic resin film. On the other hand, if the sum of the kurtosis Rku on both sides of the acrylic resin film exceeds 50, the transparency of the acrylic resin film decreases. It is more preferable that the sum of the kurtosis Rku on both sides of the acrylic resin film is 15 or more and 30 or less. If the sum of the kurtosis is 10 or more, friction between the films is easily reduced. In addition, when the films are stacked in a roll, the air trapped between the films is easily released, which is thought to suppress blocking caused by tight rolling and suppress film defects. In addition, if the sum of the kurtosis is 50 or less, diffuse reflection of light on the surface can be suppressed, preventing loss of clarity of the panel display.
[0031] Here, "blocking" refers to a state in which films are stuck together, including a state in which the films are partially melted at high temperatures and a state in which the films are perfectly overlapped. When tight winding occurs, pressure is applied to the film, causing blocking (sticking) between the films, and as a result, when the films are peeled off from each other, a strong force is used to peel them off, causing damage to the film. Therefore, by setting the kurtosis on both sides of the film to a predetermined range as in this embodiment, it is possible to suppress the sticking of the films in the film roll even if tight winding occurs, and the films can be peeled off from each other with a weak force, thereby suppressing damage to the film (film defects).
[0032] Here, the kurtosis Rku can be calculated from a roughness curve in accordance with JIS B 0601. Kurtosis Rku represents the sharpness in the height direction, where Rku=3 means that the height distribution is normal, Rku>3 means that the surface has many sharp peaks and valleys, and Rku<3 means that the surface is flat.
[0033] The kurtosis Rku (surface roughness) of the film can be measured using an optical surface roughness tester such as a laser microscope. Since the surface roughness value of the acrylic resin film of the present embodiment is smaller than the resolution of the laser microscope, sufficient measurement accuracy cannot be obtained with a lens with a small numerical aperture. Therefore, in this specification, the value measured using a lens with a numerical aperture of 0.95 or more is used.
[0034] In terms of economic efficiency and environmental load, it is preferable to add an antiblocking agent to the acrylic resin to improve the surface roughness of the film. Among them, organic fine particles are preferable in terms of affinity with the acrylic resin and dispersibility, and acrylic crosslinked particles are most preferable in terms of easy control of haze.
[0035] The static friction coefficient of the acrylic resin film, measured when one side of the film is joined to the other side, is preferably 0.8 or less, more preferably 0.7 or less, even more preferably 0.6 or less, and particularly preferably 0.5 or less. If the static friction coefficient is 0.8 or less, blocking between films during storage in a film roll can be effectively suppressed. There is no particular lower limit for the static friction coefficient, but it is preferably 0.2 or more from the viewpoint of winding slippage and meandering during production.
[0036] In the case of an acrylic resin film, the average dimensional change rate in the film longitudinal direction (MD direction) and width direction (TD direction) when left standing for 120 hours under an atmosphere of 85°C and 85% RH is preferably -2.0% or more, more preferably -1.7% or more, and even more preferably -1.5% or more. When the dimensional change rate is -2.0% or more, shrinkage over time during storage of a film roll is suppressed, and the stability of the rolled appearance over time is improved. In addition, warping and dimensional change when attached to a polarizer are alleviated, and a decrease in contrast and peripheral unevenness of a liquid crystal display device can be suppressed. The dimensional change rate may be, for example, -0.1% or less. When the dimensional change rate is -0.1% or less, even if the polarizer itself shrinks when attached to a polarizer, the acrylic resin film is likely to follow the shrinkage. The dimensional change rate when left undisturbed in an atmosphere of 85°C and 85% RH for 120 hours can be measured using a three-dimensional measuring device by leaving the acrylic resin film undisturbed in an environmental tester set to 85°C and 85% RH for 120 hours.
[0037] In this specification and claims, the dimensional change rate refers to the rate of change in the hole spacing before and after opening holes of 1 mm diameter at positions 20 mm inward from the four corners of a 90 mm x 90 mm film and leaving the film standing for 120 hours under an atmosphere of 85°C and 85% RH. Here, the rate of change in the hole spacing refers to the rate of change in the hole spacing after leaving the film standing based on the hole spacing before leaving the film standing, and is expressed by the formula [(Hole spacing after standing) - (Hole spacing before standing)] × 100 / (Hole spacing before standing) (A) It is calculated as follows.
[0038] The linear expansion coefficient of the acrylic resin film at 40 to 60°C is preferably 80 ppm or less, more preferably 72 ppm or less. If it is 80 ppm or less, the shrinkage and expansion of the film due to temperature changes during storage and transportation of the roll is suppressed, and tight winding is unlikely to occur. On the other hand, the lower limit is preferably 40 ppm or more. If the linear expansion of the film is 40 ppm or more, when laminated with a polarizer, the difference in linear expansion with other members is small, so warping is unlikely to occur.
[0039] The linear expansion coefficient can be measured, for example, using a thermomechanical analyzer TMA-4000SA manufactured by Bruker AXS. Specifically, in a nitrogen atmosphere, a film cut to 4 mm x 20 mm is heated at a rate of 2°C / min in a temperature range not exceeding the glass transition temperature under a tensile load of 3.1 g, and a chart is created in which the temperature is plotted on the X-axis and the change in the length of the film is plotted on the Y-axis. The slope in the temperature range from 40°C to 60°C during the heating and cooling process is calculated by the least squares method to obtain the linear expansion coefficient.
[0040] (Anti-blocking agent) The acrylic resin film is preferably formed from an acrylic resin composition in which an antiblocking agent is added to an acrylic resin. As the antiblocking agent, acrylic crosslinked particles are preferred from the viewpoints of compatibility with the acrylic resin, dispersibility, and transparency. Any shape of particle can be selected, but spherical particles are preferred because they are more likely to exhibit antiblocking properties.
[0041] The refractive index of the antiblocking agent is preferably 98% or more and 102% or less, and more preferably 99% or more and 101% or less, when the refractive index of the acrylic resin is 100%. The refractive index of the antiblocking agent is preferably 1.47 or more and 1.55 or less, more preferably 1.47 or more and 1.53 or less, and more preferably 1.48 or more and 1.52 or less. By using an antiblocking agent with a refractive index in this range, an acrylic resin film with high transparency can be obtained. Among them, acrylic crosslinked particles are preferable because they satisfy the above refractive index.
[0042] The polymerizable monomer forming the acrylic crosslinked particles can be selected from any (meth)acrylic acid ester and other copolymerizable monomers, but preferably contains methyl methacrylate in terms of compatibility with acrylic resin and refractive index. The content of structural units derived from methyl methacrylate in the acrylic crosslinked particles is preferably 80% by weight or more and 99% by weight or less, more preferably 83% by weight or more and 96% by weight or less. In addition, when the content of structural units derived from methyl methacrylate in the acrylic resin is high, the content of structural units derived from methyl methacrylate in the acrylic crosslinked particles is preferably high.
[0043] The acrylic crosslinked particles further contain a structural unit derived from a polyfunctional monomer containing two or more polymerizable groups in the molecule as a polymerizable monomer. The content of the polyfunctional monomer in the polymerizable monomer can be set arbitrarily, but is preferably 0.5% by weight or more and 30% by weight or less. If it is less than 0.5% by weight, the heat resistance and dispersibility of the acrylic crosslinked particles are poor. If it is more than 30% by weight, the particles may coalesce and irregularly shaped particles may be formed during the production of the acrylic crosslinked particles.
[0044] The average particle size of the acrylic crosslinked particles is preferably 0.1 μm or more and 2.5 μm or less, more preferably 0.1 μm or more and 2.0 μm or less. If it is less than 0.1 μm, it is necessary to add a large amount to exhibit antiblocking properties, which may result in poor mechanical properties and economic efficiency. If it is larger than the upper limit of 2.5 μm, clogging of the polymer filter may be induced. In addition, from the viewpoint of long-term run properties of the polymer filter, it is preferable to use one with a narrow particle size distribution and a small content of coarse particles.
[0045] The amount of the acrylic crosslinked particles added in this embodiment is preferably 0.05% by weight or more and 0.9% by weight or less, more preferably 0.07% by weight or more and 0.5% by weight or less, and even more preferably 0.1% by weight or more and 0.2% by weight or less. An amount of less than 0.05% by weight does not provide sufficient blocking prevention effect, and an amount of 0.9% by weight or less can prevent deterioration of economic efficiency and increase in haze. In addition, multiple types of particles with different particle size distributions may be mixed for the purpose of controlling slipperiness and surface properties. In this case, the amount of the acrylic crosslinked particles added is the total amount of the multiple types of particles added.
[0046] (Easy adhesion layer) The acrylic resin film of the present embodiment may have an easy-adhesion layer on one or both sides. For example, when the film is used as a polarizer protective film, the adhesive between the polarizer protective film and the polarizer can be reinforced by the adhesive when the film is bonded to the polarizer via the adhesive. It is also possible to obtain a stretched film having an easy-adhesion layer by providing an easy-adhesion layer on an unstretched film and then stretching the film.
[0047] The easy-adhesion layer used in the present embodiment can be formed using known techniques described in JP-A-2009-193061, JP-A-2010-55062, and the like. That is, for example, it can be formed from an easy-adhesion composition containing a urethane resin having a carboxyl group and a crosslinking agent. By using a urethane resin, an easy-adhesion layer having excellent adhesion between the polarizer protective film and the polarizer can be obtained. The easy-adhesion composition is preferably water-based from the viewpoint of workability and environmental protection.
[0048] (Acrylic resin) As described above, the acrylic resin film has a glass transition temperature of 120° C. or higher, and an acrylic resin having a glass transition temperature of 120° C. or higher can be suitably used as the acrylic resin film. As the acrylic resin having a glass transition temperature of 120° C. or higher, as described above, an acrylic resin having a ring structure in the main chain and an acrylic resin having no ring structure in the main chain can be used. Each ring structure will be described below.
[0049] (Acrylic resin with glutarimide ring in the main chain) The acrylic resin having a glutarimide ring as a ring structure in the main chain is a resin containing glutarimide units and methyl methacrylate units represented by the following general formula (1), and can be obtained by heating and melting an acrylic resin having an acrylate unit content of less than 1% by weight, and treating it with an imidizing agent.
[0050] [ka]
[0051] (where R 1 and R 2 each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms; R 3 represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.
[0052] The content of glutarimide rings according to the present embodiment is a value that can be measured, for example, by the following method. 1 This is done using H-NMR. The area of the peaks derived from the O-CH3 protons of methyl methacrylate at around 3.5 ppm to 3.8 ppm and the area of the NR of the glutarimide group at around 3.0 ppm to 3.3 ppm are 3 Weight conversion is performed using the molar ratio determined from the peak area derived from protons.
[0053] In the process of treating with an imidizing agent, other than methyl methacrylate, for example, methyl acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. may be used in combination, but when these are used in combination, the acrylic acid ester unit is preferably less than 1 wt%, more preferably less than 0.5 wt%, and even more preferably less than 0.3 wt%.
[0054] In addition to the above-mentioned monomers, it is also possible to copolymerize nitrile monomers such as acrylonitrile and methacrylonitrile, maleimide monomers such as maleimide, N-methylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide, and aromatic vinyl monomers such as styrene.
[0055] The structure of the methyl methacrylate resin is not particularly limited, and may be any of a linear (chain) polymer, a block polymer, a core-shell polymer, a branched polymer, a ladder polymer, and a crosslinked polymer.
[0056] In the case of a block polymer, it may be any of AB type, ABC type, ABA type, and other types of block polymers. In the case of a core-shell polymer, it may be composed of only one layer of core and one layer of shell, or each of them may be composed of multiple layers.
[0057] The method for producing polymethyl methacrylate is not particularly limited, and known methods such as emulsion polymerization, emulsion-suspension polymerization, suspension polymerization, bulk polymerization, and solution polymerization can be used, but when used in the optical field, bulk polymerization and solution polymerization are particularly preferred from the viewpoint of low impurity content. For example, it can be produced according to the methods described in JP-A-56-8404, JP-B-6-86492, JP-B-7-37482, or JP-B-52-32665.
[0058] The method for producing an acrylic resin according to the present embodiment includes a step of heating and melting a methyl methacrylate resin or an acrylic resin copolymerized with a monomer other than the methyl methacrylate monomer, and treating the acrylic resin with an imidizing agent (imidization step), thereby producing an acrylic resin having glutarimide.
[0059] The imidizing agent is not particularly limited as long as it can generate a glutarimide ring represented by general formula (1), and examples thereof include those described in WO2005 / 054311. Specific examples include aliphatic hydrocarbon group-containing amines such as ammonia, methylamine, n-propylamine, i-propylamine, n-butylamine, i-butylamine, tert-butylamine, and n-hexylamine, aromatic hydrocarbon group-containing amines such as aniline, benzylamine, toluidine, and trichloroaniline, and alicyclic hydrocarbon-containing amines such as cyclohexylamine. In addition, urea-based compounds that generate the exemplified amines by heating, such as urea, 1,3-dimethylurea, 1,3-diethylurea, and 1,3-dipropylurea, can also be used. Among these imidizing agents, it is preferable to use methylamine, ammonia, and cyclohexylamine in terms of both cost and physical properties, and it is particularly preferable to use methylamine.
[0060] Methylamine, which is gaseous at room temperature, may be used in a state of being dissolved in an alcohol such as methanol.
[0061] In this imidization step, the ratio of glutarimide units and (meth)acrylic acid ester units in the resulting acrylic resin can be adjusted by adjusting the ratio of the imidization agent added.
[0062] Furthermore, by adjusting the degree of imidization, it is possible to adjust the physical properties of the resulting acrylic resin and the transparency of the stretched film obtained by molding the acrylic resin according to this embodiment.
[0063] The imidizing agent is preferably 0.5 to 20 parts by weight per 100 parts by weight of the acrylic resin containing methyl methacrylate units. When the amount of the imidizing agent added is within this range, the imidizing agent is unlikely to remain in the resin, and the possibility of inducing appearance defects or foaming after molding is extremely low. In addition, the content of glutarimide rings in the finally obtained resin composition is also appropriate, so that the heat resistance is unlikely to decrease and appearance defects after molding are unlikely to be induced, which is preferable.
[0064] In this imidization step, in addition to the imidizing agent, a ring-closing promoter (catalyst) may be added, if necessary.
[0065] The method of heating and melting the resin and treating it with an imidizing agent is not particularly limited, and any conventionally known method can be used. For example, the acrylic resin containing the methyl methacrylate unit can be imidized by a method using an extruder, a batch-type reaction tank (pressure vessel), etc.
[0066] The extruder is not particularly limited. For example, a single screw extruder, a twin screw extruder, or a multi-screw extruder can be used. The extruder may be used alone or in series. When a twin screw extruder is used, examples include a non-intermeshing co-rotating type, an intermeshing co-rotating type, a non-intermeshing counter-rotating type, and an intermeshing counter-rotating type. Among them, an intermeshing co-rotating type twin screw extruder is preferable because it can rotate at high speed and can further promote the mixing of the imidization agent (if a ring-closing promoter is used, the imidization agent and the ring-closing promoter) with the raw material polymer.
[0067] When imidization is carried out in an extruder, for example, a methyl methacrylate resin is charged from a raw material charging section of the extruder, the resin is melted to fill the cylinder, and then an imidizing agent is injected into the extruder using an addition pump, thereby allowing the imidization reaction to proceed in the extruder.
[0068] In this case, the temperature (resin temperature), time (reaction time) and resin pressure during treatment in the extruder are not particularly limited as long as glutarimidization is possible.
[0069] When an extruder is used, it is also preferable to provide a vent hole capable of reducing the pressure to atmospheric pressure or lower in order to remove unreacted imidizing agent and by-products. With such a configuration, it is possible to remove unreacted imidizing agent, by-products such as methanol, and monomers.
[0070] When an acrylic resin containing a glutarimide ring in the main chain is produced using a batch-type reaction tank (pressure vessel), the structure of the batch-type reaction tank (pressure vessel) is not particularly limited. It is sufficient that the tank has a structure that allows the acrylic resin containing methyl methacrylate units to be melted by heating and stirred, and allows the imidization agent (when a ring-closing promoter is used, the imidization agent and the ring-closing promoter) to be added, but it is preferable that the tank has a structure that allows good stirring efficiency.
[0071] Specific examples of the imidization method include known methods such as those described in JP-A-2008-273140 and JP-A-2008-274187.
[0072] The method for producing an acrylic resin according to the present embodiment can include a step of treating with an esterifying agent in addition to the imidization step, which allows the acid value of the imidized resin obtained in the imidization step to be adjusted to within a desired range.
[0073] The esterification agent is not particularly limited as long as it can esterify the carboxyl group remaining in the molecular chain. For example, dimethyl carbonate, 2,2-dimethoxypropane, dimethyl sulfoxide, triethyl orthoformate, trimethyl orthoacetate, trimethyl orthoformate, diphenyl carbonate, dimethyl sulfate, methyl toluene sulfonate, methyl trifluoromethyl sulfonate, methyl acetate, methanol, ethanol, methyl isocyanate, p-chlorophenyl isocyanate, dimethyl carbodiimide, etc. are mentioned. Among these, dimethyl carbonate and trimethyl orthoacetate are preferred from the viewpoint of cost, reactivity, etc., and dimethyl carbonate is preferred from the viewpoint of cost.
[0074] In this imidization step, the amount of the esterification agent is preferably 0 to 30 parts by weight, more preferably 0 to 15 parts by weight, per 100 parts by weight of the acrylic resin containing methyl methacrylate units. If the amount of the esterification agent is within this range, the acid value can be adjusted to an appropriate range. On the other hand, if the amount is more than this range, unreacted esterification agent may remain in the resin, which may cause foaming or odor generation when the obtained resin is used for molding.
[0075] In addition to the esterification agent, a catalyst can be used in combination. The catalyst is not particularly limited as long as it can promote esterification. For example, aliphatic tertiary amines such as trimethylamine, triethylamine, and tributylamine can be mentioned. Among these, triethylamine is preferred from the viewpoints of cost, reactivity, etc.
[0076] In this esterification step, only the heat treatment or the like can be performed without treatment with an esterifying agent. When only the heat treatment (such as kneading or dispersing the molten resin in an extruder) is performed, some or all of the carboxyl groups can be converted to acid anhydride groups by a dehydration reaction between carboxyl groups in the acrylic resin having glutarimide rings produced as a by-product in the imidization step, or a dealcoholization reaction between a carboxyl group and an alkyloxycarbonyl group. In this case, a ring-closing promoter (catalyst) can also be used.
[0077] Even when the treatment is carried out with an esterifying agent, it is possible to promote conversion to an acid anhydride group by heat treatment.
[0078] The imide resin that has undergone the imidization step and the esterification step contains unreacted imidization agent, unreacted esterification agent, volatile components produced as by-products during the reaction, resin decomposition products, and the like, and therefore it is possible to equip the resin with a vent hole that can reduce the pressure to below atmospheric pressure.
[0079] (Acrylic resin with lactone ring in the main chain) The acrylic resin having a lactone ring as a ring structure in the main chain is not limited as long as it is a thermoplastic polymer having a lactone ring structure in the molecule (a thermoplastic polymer having a lactone ring structure introduced into the molecular chain), and the production method thereof is also not limited, but preferably, it is obtained by obtaining a polymer (a) having a hydroxyl group and an ester group in the molecular chain by polymerization (polymerization step), and then heat-treating the obtained polymer (a) to introduce a lactone ring structure into the polymer (lactone cyclization condensation step).
[0080] In the polymerization step, a monomer component containing an unsaturated monomer represented by the following general formula (2) is polymerized to obtain a polymer having a hydroxyl group and an ester group in the molecular chain.
[0081] [ka]
[0082] (However, R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.
[0083] Examples of the unsaturated monomer represented by the general formula (2) include methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, normal butyl 2-(hydroxymethyl)acrylate, and tertiary butyl 2-(hydroxymethyl)acrylate. Among them, methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylate are preferred, and methyl 2-(hydroxymethyl)acrylate is particularly preferred because of its high effect of improving heat resistance. These unsaturated monomers may be used alone or in combination of two or more.
[0084] The content of the unsaturated monomer represented by the general formula (2) in the monomer component is preferably 5% by weight to 50% by weight, more preferably 10% by weight to 40% by weight, and even more preferably 10% by weight to 30% by weight. If the content is less than 5% by weight, the heat resistance, solvent resistance, and surface hardness of the resulting lactone ring-containing polymer may decrease, and if it is more than 50% by weight, a crosslinking reaction may occur when forming the lactone ring structure, making it easy to gel, and the flowability may decrease, making it difficult to melt mold, or unreacted hydroxyl groups may remain, which may cause a further condensation reaction during molding to generate volatile substances, making it easy to cause silver streaks, or increasing the thickness direction retardation Rth.
[0085] The monomer component preferably contains other monomers other than the unsaturated monomer represented by general formula (2). The other monomers are not limited as long as they are selected within a range that does not impair the effects of the present invention, and preferred examples include (meth)acrylic acid esters, hydroxyl group-containing monomers, unsaturated carboxylic acids, and unsaturated monomers represented by the following general formula (3). The other monomers may be used alone or in combination of two or more.
[0086] [ka]
[0087] (However, R 6 represents a hydrogen atom or a methyl group, and X represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an aryl group, a -OAc group, a -CN group, or a -CO-R 7 represents an acetyl group; 7 represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.
[0088] The (meth)acrylic acid ester is not limited as long as it is a (meth)acrylic acid ester other than the unsaturated monomer represented by general formula (2), but examples thereof include acrylic acid esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, cyclohexyl acrylate, and benzyl acrylate; methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, cyclohexyl methacrylate, and benzyl methacrylate, and these may be used alone or in combination of two or more. Among them, methyl methacrylate is particularly preferred from the viewpoint of heat resistance and transparency.
[0089] When the above-mentioned (meth)acrylic acid ester is used, the content ratio thereof in the monomer component is preferably 10% by weight to 95% by weight, more preferably 10% by weight to 90% by weight, even more preferably 40% by weight to 90% by weight, and particularly preferably 50% by weight to 90% by weight, in order to fully exert the effects of the present invention.
[0090] (An acrylic resin with maleic anhydride, maleimide and glutaric anhydride structures in the main chain) In this embodiment, it is also preferable to use an acrylic resin having a maleimide or glutaric anhydride structure as a ring structure in the main chain. An example of the maleic anhydride structure is a styrene-N-phenylmaleimide-maleic anhydride copolymer. An example of the maleimide structure is an olefin-maleimide copolymer as described in JP-A-2004-45893. An example of the glutaric anhydride structure is a copolymer having a glutaric anhydride unit as described in JP-A-2003-137937.
[0091] (Acrylic resin with no ring structure in the main chain) For an acrylic resin having a glass transition temperature of 120° C. or higher, for example, a method of introducing a carboxyl group such as methacrylic acid can be mentioned. If the amount of carboxyl groups exceeds a certain amount, there is a risk of forming a crosslinked body or an increased risk of foaming during film formation, so it is preferable to suppress the amount to a certain amount or less. Specifically, the amount of carboxyl groups in the acrylic resin is preferably 0.6 mmol / g or less, and more preferably 0.4 mmol / g or less.
[0092] As the acrylic resin having a glass transition temperature of 120° C. or more, an acrylic resin having a syndiotacticity of 54% or more in triad expression can be suitably used. When the syndiotacticity of the acrylic resin is 54% or more in triad expression, the glass transition temperature of the acrylic resin increases, and the heat resistance of the acrylic resin tends to improve. The syndiotacticity of the acrylic resin in triad expression is preferably 55% or more, more preferably 56% or more, and even more preferably 57% or more. In addition, the syndiotacticity of the acrylic resin in triad expression is preferably 67% or less, more preferably 65% or less, and even more preferably 63% or less, from the viewpoints of the molding temperature of the acrylic resin, the toughness of the molded body, and secondary processability.
[0093] The syndiotacticity of acrylic resins, as expressed by triads, is the proportion of three structural unit chains (triads) that are rr. In addition, in chains of two structural units (diads), those with the same configuration are called meso (m) and those with the opposite configuration are called racemo (r).
[0094] The synthesis method of an acrylic resin having a syndiotacticity of 55% or more in terms of triads is not particularly limited, but examples thereof include anionic polymerization and radical polymerization. Among these, radical polymerization is preferred (see, for example, International Publication No. WO 2023 / 238885 and International Publication No. WO 2023 / 238886). In the radical polymerization method, since an organometallic compound as a polymerization initiator and an organic solvent as a medium used in the anionic polymerization method are not used, impurities are less likely to remain, and it is preferable from the viewpoint of the environment. Here, the glass transition temperature and syndiotacticity in terms of triads of the acrylic resin can be controlled by the polymerization temperature of the acrylic resin. For example, by lowering the polymerization temperature of the acrylic resin, the glass transition temperature of the acrylic resin increases and the syndiotacticity of the acrylic resin increases. In addition, the glass transition temperature of the acrylic resin can also be controlled by the molecular weight of the acrylic resin.
[0095] The content of structural units derived from methyl methacrylate in an acrylic resin having a triad syndiotacticity of 54% or more is preferably 98% by weight or more, more preferably 99% by weight or more, and even more preferably 100% by weight.
[0096] Monomers other than methyl methacrylate that constitute an acrylic resin having a syndiotacticity of 54% or more, expressed as a triad, are not particularly limited, and examples thereof include alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate; aryl acrylates such as phenyl acrylate; cycloalkyl acrylates such as cyclohexyl acrylate and norbornenyl acrylate; alkyl methacrylates other than methyl methacrylate, such as ethyl methacrylate, propyl methacrylate, and butyl methacrylate; aryl methacrylates such as phenyl methacrylate; cycloalkyl methacrylates such as cyclohexyl methacrylate and norbornenyl methacrylate; aromatic vinyl compounds such as styrene and α-methylstyrene; acrylamide; methacrylamide; acrylonitrile; and methacrylonitrile.
[0097] (Other characteristics of acrylic resins) Other characteristics of the acrylic resin having a ring structure in the main chain and the acrylic resin not having a ring structure in the main chain will be described below. Hereinafter, the term "acrylic resin" refers to at least one of the acrylic resin having a ring structure in the main chain and the acrylic resin not having a ring structure in the main chain.
[0098] The weight-average molecular weight of the acrylic resin is preferably from 50,000 to 200,000, and more preferably from 90,000 to 150,000. When the weight-average molecular weight of the acrylic resin is 50,000 or more, the mechanical properties of a molded product of the acrylic resin tend to improve, and when it is 200,000 or less, the moldability of the acrylic resin tends to improve.
[0099] The weight average molecular weight of the acrylic resin may be 400,000 or more. When the weight average molecular weight of the acrylic resin is 400,000 or more, the mechanical properties of the molded body of the acrylic resin tend to be further improved, and for example, a resin film with excellent bending resistance can be obtained. In this case, the weight average molecular weight of the acrylic resin is preferably 600,000 or more, more preferably 700,000 or more, and even more preferably 800,000 or more. In addition, from the viewpoint of moldability of the acrylic resin, the weight average molecular weight of the acrylic resin is preferably 2.5 million or less, more preferably 2 million or less, even more preferably 1.5 million or less, and particularly preferably 1.2 million or less.
[0100] The ratio of the weight average molecular weight to the number average molecular weight of the acrylic resin (dispersity) is preferably 1.6 to 2.5, more preferably 1.7 to 2.2. When the dispersity of the acrylic resin is 1.6 or more, the fluidity of the acrylic resin tends to improve and the resin tends to be easily molded, and when the dispersity is 2.5 or less, the mechanical properties of the molded product of the acrylic resin, such as impact resistance, toughness, and bending resistance, tend to improve.
[0101] The number average molecular weight and weight average molecular weight of the acrylic resin are values calculated in terms of standard polystyrene measured by gel permeation chromatography (GPC). The number average molecular weight and weight average molecular weight of the acrylic resin can be controlled by the type and amount of the polymerization initiator and chain transfer agent used in synthesizing the acrylic resin.
[0102] (Acrylic resin composition) The acrylic resin film may be an acrylic resin composition obtained by adding additives to an acrylic resin, or an antiblocking agent and an additive may be used in combination. The additives may include commonly used antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, specific wavelength absorbers or specific wavelength absorbing dyes for cutting blue light, light resistance stabilizers such as radical scavengers, retardation adjusters, catalysts, plasticizers, lubricants, antistatic agents, colorants, shrinkage inhibitors, antibacterial and deodorant agents, fluorescent brighteners, compatibilizers, etc., either alone or in combination of two or more, as long as they do not impair the object of the present invention.
[0103] Examples of the ultraviolet absorbent include triazine-based compounds, benzotriazole-based compounds, benzophenone-based compounds, cyanoacrylate-based compounds, benzoxazine-based compounds, and oxadiazole-based compounds. Among these, triazine-based compounds are preferred from the viewpoint of ultraviolet absorbing performance relative to the amount added and volatility when melt extrusion is performed.
[0104] Regarding the retardation adjusting agent, in the case of imparting a negative retardation, it is sufficient if it is a compound having a styrene skeleton, and an example of this is an acrylonitrile-styrene copolymer.
[0105] The method for mixing the acrylic resin and the antiblocking agent is not particularly limited, and any conventionally known method can be used, such as feeding the mixture to an extruder using a gravimetric feeder and melt-kneading the mixture, or mixing the acrylic resin and the antiblocking agent in the form of a solution in a solvent having excellent compatibility with each other.
[0106] When mixing is performed using an extruder, the extruder to be used is not particularly limited, and various extruders can be used. Specifically, a single screw extruder, a twin screw extruder, or a multi-screw extruder can be used. Among them, it is preferable to use a twin screw extruder. The twin screw extruder allows a wide degree of freedom in the conditions for uniformly mixing the acrylic resin and the antiblocking agent. In addition, the acrylic resin and the antiblocking agent may be charged and mixed from the upstream side of the extruder using a raw material charging hopper or the like, or only the antiblocking agent may be charged and mixed from the middle of the extruder using a side feeder, a gravimetric feeder, or the like. Alternatively, the antiblocking agent may be made into a master batch in advance using a separate extruder and used.
[0107] A filter can be installed at the end of the extruder to reduce foreign matter in the resin. A gear pump is preferably installed before the filter to increase the pressure of the (A) acrylic resin / acrylic resin composition. As for the type of filter, a stainless steel leaf disk filter capable of removing foreign matter from the molten polymer is preferably used, and as the filter element, a fiber type, a powder type, or a combination of these types is preferably used.
[0108] (Method of manufacturing acrylic resin film) An embodiment of the method for producing a stretched film of the present invention will be described below, but the present invention is not limited thereto. In other words, any method known in the art can be used as long as it is a method that can produce a film by molding the acrylic resin composition of the present embodiment.
[0109] Specifically, examples of the molding method include injection molding, melt extrusion molding, inflation molding, blow molding, compression molding, etc. The film according to the present embodiment can be produced by dissolving the acrylic resin composition according to the present embodiment in a solvent capable of dissolving the composition, and then molding the resulting solution by a solution casting method or a spin coating method.
[0110] Among these, it is preferable to use the melt extrusion method which does not use a solvent, since the melt extrusion method can reduce the manufacturing cost and the burden on the global environment and working environment caused by the solvent.
[0111] When the acrylic resin composition of the present embodiment is formed into a film by melt extrusion, the acrylic resin composition of the present embodiment is first pre-dried and then fed to an extruder, where the acrylic resin composition is heated and melted. The acrylic resin composition is then fed to a die such as a T-die through a gear pump or a filter. The acrylic resin composition fed to the T-die is then extruded as a sheet-like molten resin, and cooled and solidified using a cooling roll or the like to obtain an unstretched film (also called a raw film). At this time, in order to improve the surface properties (smoothness) of the film, it is also possible to sandwich the film between flexible rolls equipped with a metal roll and a metallic elastic outer cylinder.
[0112] When the acrylic resin composition of the present embodiment is formed into an unstretched film by the solution casting method, the acrylic resin composition of the present embodiment is dissolved together with an organic solvent, and the solution is cast on a support and dried by heating to produce an unstretched film. The solvent that can be used in the solution casting method can be selected from known solvents. Halogenated hydrocarbon solvents such as methylene chloride and trichloroethane are preferred solvents because they easily dissolve the acrylic resin of the present embodiment and have a low boiling point. In addition, non-halogen solvents with high polarity such as dimethylformamide and dimethylacetamide can also be used. In addition, aromatic solvents such as toluene, xylene, and anisole, cyclic ether solvents such as dioxane, dioxolane, tetrahydrofuran, and pyran, and ketone solvents such as methyl ethyl ketone can also be used. These solvents may be used alone. In addition, a mixture of multiple types may be used. The amount of solvent used can be any amount as long as it can dissolve the thermoplastic resin to an extent that casting can be performed sufficiently. In this specification, "dissolved" means that the resin is present in the solvent in a homogeneous state to an extent that casting can be performed sufficiently. It is not necessary that the solute is completely dissolved in the solvent. The resin concentration in the solution is preferably 1% by weight to 90% by weight, more preferably 5% by weight to 70% by weight, and further preferably 10% by weight to 50% by weight. A preferred support may be an endless belt made of stainless steel. Alternatively, a film such as a polyimide film or a polyethylene terephthalate film may be used.
[0113] The acrylic resin film of the present embodiment is obtained by stretching an unstretched film (also called a raw film). By stretching the unstretched film, it is possible to produce a stretched film of a desired thickness, and further, it is possible to improve the mechanical properties of the stretched film.
[0114] As the stretching method, a conventionally known method can be used. For example, an unstretched raw film formed by melt extrusion can be stretched uniaxially or biaxially to produce a film of a predetermined thickness. In order to impart excellent mechanical properties to the stretched film in both the longitudinal direction (MD) and the width direction (TD), biaxial stretching is preferred. The biaxial stretching method may be simultaneous biaxial stretching or sequential biaxial stretching.
[0115] The stretching ratio (in the case of biaxial stretching, both in the MD and TD directions of the film) is preferably 1.5 to 3.0 times, and more preferably 1.8 to 2.8 times. If the stretching ratio is within this range, the mechanical properties of the film due to stretching can be sufficiently improved. In addition, the degree of orientation does not increase too much, and the dimensional change when left standing for 120 hours under an atmosphere of 85°C and 85% RH can be reduced, and further, there is little possibility that the peel strength when attached to a polarizer will decrease. The stretching speed is preferably 1.1 times / min or more, and more preferably 5 times / min or more. In addition, it is preferably 100 times / min or less, and more preferably 50 times / min or less. In the case of sequential biaxial stretching, the stretching speed in the first stage and the stretching speed in the second stage may be the same or different. In the sequential biaxial stretching, the first stage stretching is usually in the longitudinal direction (MD direction), and the second stage stretching is in the transverse direction (TD direction).
[0116] The stretching temperature is not particularly limited, but is preferably Tg+7°C to Tg+50°C, and more preferably Tg+10°C to Tg+40°C. When the stretching temperature is Tg+7°C or higher, the risk of breakage during the stretching process can be suppressed. On the other hand, when the stretching temperature is Tg+50°C or lower, sufficient molecular orientation is obtained, and the decrease in mechanical strength of the film can be suppressed. When the stretching temperature is high within the above range, the molecular orientation is relaxed, so that the mechanical strength decreases, while the dimensional change in an atmosphere of 85°C and 85% RH is small. In addition, in the case of a film containing an antiblocking agent, when stretched at a low temperature, particles tend to float to the surface, and surface roughness, slipperiness, and external haze tend to appear. Those skilled in the art can set the stretching conditions arbitrarily in consideration of the above balance.
[0117] The acrylic resin film of this embodiment is wound into a roll by a known method. With the film of this embodiment, defects caused by blocking between films are unlikely to occur even when the film width is wide or the winding length is long. In addition, it is more effective to combine it with knurling of the end portion, which has been used as a countermeasure against blocking.
[0118] (Application) When the acrylic resin film of the present embodiment is used as a polarizer protective film, it is bonded to a polarizer to form a polarizing plate. The polarizer is not particularly limited, and any conventionally known polarizer can be used. For example, a polarizer obtained by incorporating iodine into stretched polyvinyl alcohol can be used.
[0119] This polarizing plate can be further laminated with various films and suitably used in the field of displays such as liquid crystal displays and organic EL displays, although its applications are not limited to these. EXAMPLES
[0120] The present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited thereto. Those skilled in the art can make various changes, modifications, and alterations without departing from the scope of the present invention.
[0121] (Surface roughness) The surface roughness of the acrylic resin film was measured using a laser microscope LEXT OLS5100 manufactured by Evident in accordance with JIS B0601:2013. Specifically, first, a confocal image of the film in an area of 257 μm × 257 μm was captured using an objective lens with a magnification of 50 times and a numerical aperture of 0.95. Next, three evaluation lines were drawn at equal intervals in each of the MD and TD directions to extract a roughness curve. From the obtained roughness curve, the kurtosis Rku was calculated using analysis software, and the average value at the measurement position was calculated. The measurement was performed five times at different measurement positions, and the average value was adopted as the surface roughness. However, if partial abnormalities such as scratches were clearly observed in the image, they were not included in the measurement value, and the measurement was performed again while avoiding the abnormal parts.
[0122] (Static friction coefficient) The static friction coefficient of the acrylic resin film was measured using Imada's digital force gauge ZTS-5N and friction coefficient measurement jig COF-2N-V in accordance with JIS K7125:1999. Specifically, side A of the film was fixed on a smooth stainless steel plate, side B of the film was attached to a 60 x 60 mm sled weighing 200 g with double-sided tape, and the load when the sled was moved at a speed of 100 mm / min via a pulley was read with a load cell to calculate the static friction coefficient. The measurement was performed five times by replacing the film piece, and the average value was calculated.
[0123] (Haze, internal haze) The haze of the acrylic resin film was measured in accordance with JIS 7136: 2000 using a haze meter NDH2000 manufactured by Nippon Denshoku Kogyo Co., Ltd. The internal haze of the acrylic resin film was measured by placing the acrylic resin film in a glass cell for measuring liquid so that distilled water was in contact with both sides of the acrylic resin film.
[0124] (glass transition temperature) The glass transition temperature of the acrylic resin or acrylic resin film was measured using 10 mg of the acrylic resin or acrylic resin composition. Specifically, the glass transition temperature was determined by the midpoint method using a differential scanning calorimeter (manufactured by Hitachi High-Tech Science, DSC7000X) under a nitrogen atmosphere at a temperature increase rate of 20°C / min.
[0125] (Dimensional change rate) A 90mm x 90mm acrylic resin film was cut out with a cutter, and holes were punched 20mm inward from the four corners of the film diagonally from the four corners with a 1mm diameter punch, and the hole spacing was measured using a Mitutoyo MF201 three-dimensional measuring device. The stretched film after the hole spacing was then left to stand for 120 hours in a Nagano Science LH-20 environmental tester set at 85°C and 85% RH, and the hole spacing was measured again. The dimensional change rate was calculated from the hole spacing before and after standing in an atmosphere of 85°C and 85% RH using formula (A).
[0126] (Refractive Index of Acrylic Resin Composition and Acrylic Crosslinked Particles) First, the refractive index of the acrylic resin composition was determined in accordance with JIS K7142:2014 as follows. Specifically, the acrylic resin composition was melt-pressed at 240°C to form a film having a thickness of 100 μm, and the refractive index (wavelength 589 nm) of the obtained film was measured under conditions of 23°C using a refractometer (Digital Abbe Refractometer DR-M2, manufactured by Atago Co., Ltd.). The obtained refractive index was defined as the refractive index of the acrylic resin composition.
[0127] Next, the refractive index of the acrylic crosslinked particles was obtained by the following method using a mixture of a halogen-based high refractive index liquid and a low refractive index liquid such as methanol, with the ratio being changed. Here, the acrylic crosslinked particles were dispersed in the mixture, and when the refractive index of the mixture and the acrylic crosslinked particles did not match, the dispersion became cloudy, and when the refractive index of the mixture and the acrylic crosslinked particles matched, the liquid became transparent. Therefore, the refractive index of the mixture when it became transparent was taken as the refractive index of the acrylic crosslinked particles.
[0128] <Production of acrylic resin> (Production Example of Acrylic Resin 1) The extruder used was a 40 mm diameter co-rotating intermeshing twin screw extruder (L / D=90). The set temperature of each temperature control zone of the extruder was 250-280°C, and the screw speed was 85 rpm. After the methyl methacrylate resin was melted and filled by the kneading block, 1.8 parts by weight of monomethylamine (manufactured by Mitsubishi Gas Chemical) was injected from the nozzle per 100 parts by weight of the methyl methacrylate resin. The resin that came out as a strand from the die provided at the extruder outlet was cooled in a water tank and pelletized with a pelletizer to obtain resin (I). Next, the set temperature of each temperature control zone of the extruder was set to 240-260°C using a 40 mm diameter co-rotating intermeshing twin screw extruder. 0.56 parts by weight of dimethyl carbonate was injected from the nozzle per 100 parts by weight of the methyl methacrylate resin to reduce the carboxyl group in the resin. By-products and excess dimethyl carbonate after the reaction were removed. The resin that came out as strands from the die provided at the outlet of the extruder was cooled in a water tank and then pelletized in a pelletizer to obtain acrylic resin 1 having glutarimide rings. The glass transition temperature of the acrylic resin 1 was 123°C, Mw was 81,000, and Mw / Mn was 1.59.
[0129] (Calculation of ring structure content) The obtained acrylic resin 1 Measurements were performed using a H-NMR BRUKER AvanceIII (400MHz). The molar ratio of the target ring structure part to the other parts was converted into weight and calculated. Specifically, in the case of glutarimide, the molar ratio was calculated by converting the weight from the area A of the peak derived from the O-CH3 proton of methyl methacrylate around 3.5 to 3.8 ppm and the area B of the peak derived from the N-CH3 proton of glutarimide around 3.0 to 3.3 ppm, and the ring structure content was calculated to be 6% by weight.
[0130] Example 1 A mixture containing the acrylic resin 1 produced in the above acrylic resin production example and 0.1 wt% of acrylic crosslinked particles (MX80H3wT, manufactured by Soken Chemical Industries, Ltd., refractive index 1.49) having an average particle size of 0.8 μm as an antiblocking agent (AB agent) was kneaded in a 15 mm diameter intermeshing co-rotating twin screw extruder (L / D=45). The resin that came out as strands from a die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain an acrylic resin composition. The refractive index of the acrylic resin composition was 1.49.
[0131] The obtained acrylic resin composition was dried at 100°C for 5 hours, and then formed into a film using a 15mm diameter intermeshing type co-rotating twin screw extruder (L / D=45) equipped with a T-die at the extruder outlet. The sheet-like molten resin extruded from the T-die at the extruder outlet was cooled with a cooling roll to obtain a raw film with a width of 160 mm and a thickness of 160 μm. In this case, the surface in contact with the cast roll was defined as side B, and the other side was defined as side A.
[0132] The glass transition temperature of the original film was measured according to the above-mentioned method and was found to be 123°C.
[0133] The obtained raw film was simultaneously biaxially stretched at a stretch ratio of 2 times (vertical and horizontal) at 145° C. using a biaxial stretching device (IMC-1905) manufactured by Imoto Manufacturing Co., Ltd. to produce a stretched film (acrylic resin film).
[0134] (Blocking test) Ten test pieces (acrylic resin films) measuring 100 mm x 100 mm were stacked, and then 1 kg of pressure was applied from above and left at 60°C for 2 hours. After that, the pieces were left to cool at 23°C for 1 hour, and the condition of the acrylic resin films was visually checked and the acrylic resin films were peeled off by hand and evaluated according to the following criteria. 1: The films are strongly adhered to each other, and when peeled off, a mark is left on the film. 2: The films are adhered to each other, so that no marks are left on the film when it is peeled off. 3: No adhesion between films is observed.
[0135] Table 1 shows the evaluation results of Rku, static friction coefficient, haze, internal haze, glass transition temperature, dimensional change rate and blocking test.
[0136] Example 2 An acrylic resin composition (refractive index 1.49) was obtained in the same manner as in Example 1, except that 0.04% by weight of acrylic crosslinked particles (manufactured by Sekisui Chemical Co., Ltd., xx-6390Z, refractive index 1.49) having an average particle diameter of 0.15 μm was added in addition to 0.1% by weight of acrylic crosslinked particles having an average particle diameter of 0.8 μm, and an acrylic resin film was obtained using the acrylic resin composition.
[0137] Comparative Example 1 An acrylic resin film was obtained in the same manner as in Example 1, except that the AB agent was not added.
[0138] Comparative Example 2 An acrylic resin film was obtained in the same manner as in Example 1, except that the amount of the AB agent added was 0.03% by weight.
[0139] Comparative Example 3 An acrylic resin film was obtained in the same manner as in Example 1, except that the amount of the AB agent added was 1.0 wt %.
[0140] Comparative Example 4 An acrylic resin film was obtained in the same manner as in Example 1, except that Parapet HM (manufactured by Kuraray, refractive index 1.49, Tg 118°C, Mw = 78,000, Mw / Mn = 1.72), a PMMA resin not containing a ring structure, was used as acrylic resin 2 instead of acrylic resin 1.
[0141] [Table 1]
[0142] From Table 1, it can be seen that the acrylic resin films of Examples 1 and 2 are excellent in transparency and heat resistance, and can prevent blocking during film roll storage. In contrast, the acrylic resin films of Comparative Examples 1 and 2 have a sum of kurtosis Rku on both sides of 7.8 and 9.6, respectively, and therefore cannot prevent blocking during film roll storage. The acrylic resin film of Comparative Example 3 has a sum of kurtosis Rku on both sides of 74.0, and therefore has reduced transparency. The acrylic resin film of Comparative Example 4 has a glass transition temperature of 118°C, and therefore has reduced heat resistance.
[0143] <Production of acrylic resin> (Production Example of Acrylic Resin 3) In a 4L glass reactor equipped with an agitator having an H-shaped agitator blade, 150 parts by weight of deionized water, 0.20 parts by weight of calcium phosphate tribasic as a dispersant, 0.0075 parts by weight of sodium α-olefin sulfonate, and 0.30 parts by weight of sodium chloride were charged. Next, under a nitrogen atmosphere, while stirring at 250 rpm, 100 parts by weight of methyl methacrylate (MMA), 0.289 parts by weight of n-octyl mercaptan as a chain transfer agent, and 0.065 parts by weight of 2,2'-azobis(isobutyrate)dimethyl (manufactured by Fujifilm Wako Pure Chemical Industries, V-601) as a polymerization initiator were added to the reactor. Next, the liquid temperature in the reactor was raised to 70°C to start polymerization, and 2 hours after the start of polymerization, 0.10 parts by weight of calcium phosphate tribasic was added to the reactor. At this time, an exothermic peak associated with the gel effect was observed 4 hours and 20 minutes after the start of polymerization. Next, 7 hours after the start of polymerization, heating was started, and the liquid temperature in the reactor was raised to 95°C. The conversion rate 7 hours after the start of polymerization was 93%. Next, 2 hours after the liquid temperature in the reactor reached 95°C, the liquid temperature in the reactor was cooled to room temperature to terminate the polymerization, and an acrylic resin dispersion was obtained. The conversion rate at the end of polymerization was 99%.
[0144] The acrylic resin dispersion was washed with 1N hydrochloric acid in an amount of 0.1 times by weight relative to the weight of the charged monomer, and then washed with water to remove the dispersant. Next, the washed acrylic resin dispersion was dehydrated and dried to obtain beads of acrylic resin 3. The acrylic resin 3 had a glass transition temperature of 120°C, a triad syndiotacticity of 57%, Mw of 83,000, Mw / Mn of 1.63, and a content of structural units derived from methyl methacrylate of 100% by weight.
[0145] (Conversion rate) The ratio of the solid weight of the acrylic resin after drying for 30 minutes in an oven heated to 150°C to the weight of the charged monomer by the gravimetric method, that is, the formula (Weight of acrylic resin solids) x 100 / (Weight of charged monomer) The conversion rate was calculated from the above.
[0146] (Syndiotacticity in triads) Using a nuclear magnetic resonance spectrometer (Bruker, AVANCEIII 400MHz), the acrylic resin was measured in a deuterated chloroform solution at 22°C with 16 cumulative cycles. 1 H-NMR spectrum was measured. Next, the area (X) of the region from 0.60 to 0.95 ppm and the area (Y) of the region from 0.60 to 1.25 ppm when tetramethylsilane (TMS) was set to 0 ppm were measured, and then the formula (X / Y)×100 The syndiotacticity of the triad was calculated by the following formula:
[0147] (Weight average molecular weight, number average molecular weight and dispersity) The weight average molecular weight (Mw), number average molecular weight (Mn) and dispersity (Mw / Mn) of the acrylic resin were calculated by gel permeation chromatography (GPC) under the following conditions using a sample solution prepared by dissolving 20 mg of the acrylic resin in 10 mL of tetrahydrofuran. Measuring equipment: HLC-8420GPC (Tosoh) Detector: RI detector Eluent: Tetrahydrofuran Guard column: TSKgel guard column SuperH-L (manufactured by Tosoh) Analytical columns: TSKgel SuperH5000, SuperH4000, SuperH3000, SuperH2000 (Tosoh) (in series) Eluent flow rate: 0.6mL / min Measurement temperature: 40℃ Standard material: Standard polystyrene (manufactured by Tosoh)
[0148] Example 3 An acrylic resin film was obtained in the same manner as in Example 1, except that acrylic resin 3 was used instead of acrylic resin 1.
[0149] Table 2 shows the evaluation results of Rku, static friction coefficient, haze, internal haze, glass transition temperature, dimensional change rate and blocking test.
[0150] Example 4 An acrylic resin film was obtained in the same manner as in Example 3, except that 0.12 wt% of acrylic crosslinked particles (J-3PY, refractive index 1.49, manufactured by Negami Chemical Industries, Ltd.) having an average particle size of 1.2 μm was used instead of 0.1 wt% of acrylic crosslinked particles having an average particle size of 0.8 μm.
[0151] Comparative Example 5 An acrylic resin film was obtained in the same manner as in Example 3, except that the AB agent was not added.
[0152] [Table 2]
[0153] From Table 2, it can be seen that the acrylic resin films of Examples 3 and 4 are excellent in transparency and heat resistance, and can prevent blocking during film roll storage. In contrast, the acrylic resin film of Comparative Example 5 cannot prevent blocking during film roll storage because the sum of the kurtosis Rku on both sides is 7.1.
Claims
1. An acrylic resin film containing an acrylic resin as a main component and containing acrylic crosslinked particles, The acrylic crosslinked particles have an average particle size of 0.1 μm or more and 2.0 μm or less, The acrylic resin film contains 0.05% by weight or more and 0.2% by weight or less of the acrylic crosslinked particles, The acrylic resin film has a glass transition temperature of 120° C. or higher, The acrylic resin film has a sum of kurtosis Rku on both sides of the acrylic resin film of 10 or more and 50 or less, a haze of the acrylic resin film of 2.0% or less, and an internal haze of the acrylic resin film of 0.5% or less.
2. 2. The acrylic resin film according to claim 1, wherein the static friction coefficient between one surface and the other surface of the acrylic resin film is 0.8 or less.
3. 3. The acrylic resin film according to claim 1, wherein the acrylic resin contains at least one ring structure selected from the group consisting of a lactone ring structure, a glutarimide structure, a glutaric anhydride structure, an N-substituted maleimide structure, and a maleic anhydride structure.
4. The acrylic resin film according to claim 1 or 2, wherein the acrylic resin has a syndiotacticity of 54% or more in terms of triad expression.
5. An acrylic resin film as described in claim 1 or 2, wherein the internal haze of the acrylic resin film is 0.2% or less.
6. An acrylic resin film as described in claim 1 or 2, wherein the internal haze of the acrylic resin film is 0.1% or less.
7. An acrylic resin film as described in claim 1 or 2, wherein the haze of the acrylic resin film is 1.0% or less.
8. An acrylic resin film as described in claim 1 or 2, which is a biaxially stretched film.
9. An acrylic resin film as described in claim 1 or 2, wherein the ratio of the weight average molecular weight to the number average molecular weight of the acrylic resin is 1.6 or more and 2.5 or less.
10. 3. The acrylic resin film according to claim 1, which has a dimensional change rate of −2.0% or more and −0.1% or less when left standing in an atmosphere of 85° C. and 85% RH for 120 hours.
11. A polarizing plate comprising the acrylic resin film according to claim 1 .
12. A liquid crystal display panel comprising the polarizing plate according to claim 11.
Citation Information
Patent Citations
Method for producing optical film
JP2010275434A
Method for producing optical film, and optical film
JP2016203416A
Optical film and method for producing the same
JP2017177665A
Modified methacryl rein and molded body
JP2017179103A
Optical film and method of manufacturing the same
JP2017181990A